Pachoumi, E., Edwards, M.J. (eds.) (2018). Praying and Contemplating in Late Antiquity. Religious and Philosophical Interactions - Patzelt, Maik (ARYS. Antigüedad: Religiones y Sociedades, 2020)
PACHOUMI, ELENI and EDWARDS, MARK (eds.) (2018). Praying and Contemplating in Late Antiquity Religious and Philosophical Interactions, Studies and Texts in Antiquity and Christianity 113. Tübingen: Mohr Siebeck. 229 pp., 79,00€ [ISBN 978-3-1615-6119-1] [Book review]